2007
DOI: 10.1001/jama.298.10.1163
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Homocysteine Lowering on Mortality and Vascular Disease in Advanced Chronic Kidney Disease and End-stage Renal Disease

Abstract: N 1969, MCCULLY 1 PROPOSED THAT high plasma total homocysteine concentration caused severe atherothrombotic disease and death in adolescents with homocystinuria. Folic acid, vitamin B 6 , and vitamin B 12 play critical rolesinthemetabolismofhomocysteine. 2 Treatment with large doses of folic acid, pyridoxine hydrochloride (vitamin B 6 ), and cyanocobalamin (vitamine B 12 ) lowered the homocysteine levels and dramatically reduced mortality in these patients. 3 In the last 30 years, numerous case-control and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
302
2
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 418 publications
(319 citation statements)
references
References 35 publications
11
302
2
4
Order By: Relevance
“…2 -5. As noted, Jamison et al (20) reported myocardial infarction as the cardiovascular event. The RR estimated were not statistically significantly different for any outcomes.…”
Section: Relative Risk For Chd Cvd Stroke and All-cause Mortalitymentioning
confidence: 87%
See 4 more Smart Citations
“…2 -5. As noted, Jamison et al (20) reported myocardial infarction as the cardiovascular event. The RR estimated were not statistically significantly different for any outcomes.…”
Section: Relative Risk For Chd Cvd Stroke and All-cause Mortalitymentioning
confidence: 87%
“…For example, the plausibility of a link between the levels of Hcy and the risk of CVD was supported by a number of studies. (12) Folic acid: 5 mg/d or 5 mg, every other day 35路0 13路1 2 15路1 2 49路3 Righetti et al (14) Folic acid: 15 mg/d 27 13路0 2 2路4 2 8路9 Vianna et al (17) Folic acid: 10 mg, three times a week 23路5 15 2 10路5 2 44 Jamison et al (20) Folic Vit, vitamin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations